2005
DOI: 10.1051/agro:2004055
|View full text |Cite
|
Sign up to set email alerts
|

Measuring of some selected herbicides in paddy surface water in the Saijo Basin, Western Japan

Abstract: An analysis of the dissipation of herbicides was done in paddy water and in drainage channels of farm paddies as well as in experimental plots. A field study was conducted in three selected paddy farms of Higashi Hiroshima and an experiment was carried out in the Hiroshima Prefecture Agriculture Research Center in the paddy season of the year 2002. The herbicides were mefenacet, thiobencarb, pyributicarb and cyhalofop-butyl. The sample water was analyzed by using gas chromatography after solid phase extraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Thorough searches using the databases of Thomson Scientific (2007) and GeNii (2007) Kajinashi River, Ibaraki (Tada & Hatakeyama 2000) Sakura River, Ibaraki (Ueji & Inao 2001) Kozakura River, Ibaraki (Nakano, et al 2004) Sugao Marsh, Ibaraki (Kawakami, et al 2005; Lake Kasumigaura, Ibaraki (Nohara & Iwauma 1996a;1996b) Lake Biwa, Shiga Okamura, et al 2002) Lake Kojima, Okayama (Okamura, et al 1999) Yodo River, Osaka (Yamaguchi, et al 1992) Saijo Basin, Hiroshima (Parveen, et al 2005a;2005b) Kurose River, Hiroshima (Derbalah, et al 2003) Minaga River & Minaga Reservoir, Hiroshima (Itagaki, et al 2000) Map source: http://www.craftmap.box-i.net Kagoshima (This study) Fig. 1 Study sites of most published papers on pesticide residue concentrations in freshwater areas around Japan for information regarding concentrations of pesticides in freshwater areas in southern Japan yielded negative results.…”
Section: Introductionmentioning
confidence: 99%
“…Thorough searches using the databases of Thomson Scientific (2007) and GeNii (2007) Kajinashi River, Ibaraki (Tada & Hatakeyama 2000) Sakura River, Ibaraki (Ueji & Inao 2001) Kozakura River, Ibaraki (Nakano, et al 2004) Sugao Marsh, Ibaraki (Kawakami, et al 2005; Lake Kasumigaura, Ibaraki (Nohara & Iwauma 1996a;1996b) Lake Biwa, Shiga Okamura, et al 2002) Lake Kojima, Okayama (Okamura, et al 1999) Yodo River, Osaka (Yamaguchi, et al 1992) Saijo Basin, Hiroshima (Parveen, et al 2005a;2005b) Kurose River, Hiroshima (Derbalah, et al 2003) Minaga River & Minaga Reservoir, Hiroshima (Itagaki, et al 2000) Map source: http://www.craftmap.box-i.net Kagoshima (This study) Fig. 1 Study sites of most published papers on pesticide residue concentrations in freshwater areas around Japan for information regarding concentrations of pesticides in freshwater areas in southern Japan yielded negative results.…”
Section: Introductionmentioning
confidence: 99%
“…The study has proven that the excessive use of pesticides can contaminate water and soil indicated by the increasing of detected-metal content in water and soil [5]. According to [1], the exceed dosage of insecticides could kill the natural enemies of pest which generate adverse side effects.Untargeted-living organism could die due to poisoning whereas the other living organism around plants plays an important role in maintaining the ecosystem. The natural enemies could die resulting the poisoning soil and water.…”
Section: Resultsmentioning
confidence: 99%
“…This condition generates the environmental pollution of insecticide residues on the field-soil. Pesticides are applied to prevent, reduce or control pests that potentially reduce the number of productivities of rice per hectare, and even cause the crop failure known aspuso [1]. The loss of production yield could be done by attacking of plant disturbing organisms and pestwhich reduce ± 30% and 20-25% of yield production every year [2].…”
Section: Introductionmentioning
confidence: 99%
“…7,8) The DT 50 of simetryn was also estimated to be about 3 days from the data of Inao et al 10) For thiobencarb, the DT 50 values were slightly more than 2 days in this study, comparable with recent studies in Japanese paddies. [7][8][9] Also in Japanese paddies, Amano et al 13) provided a DT 50 of about 4 days for thiobencarb and Parveen et al 14) determined the DT 50 as 2.9 and 6.9 on a large farm and in an experimental plot, respectively. In other studies from different countries, half-lives of thiobencarb have been reported to be from 3.4 to 9 days.…”
Section: Pesticide Behavior In Paddy Watermentioning
confidence: 99%